Current Ventilator and Oxygen Management during General Anesthesia: A Multicenter, Cross-sectional Observational Study. (July 2018) - Suzuki, Satoshi; Mihara, Yuko; Hikasa, Yukiko; Okahara, Shuji; Ishihara, Takuma; Shintani, Ayumi; Morimatsu, Hiroshi; Sato, Akiko; Kusume, Sachio; Hidaka, Hidekuni; Yatsuzuka, Hidehiko; Okawa, Masahiro; et al.
Abstract : Background: Intraoperative oxygen management is poorly understood. It was hypothesized that potentially preventable hyperoxemia and substantial oxygen exposure would be common during general anesthesia. Methods: A multicenter, cross-sectional study was conducted to describe current ventilator management, particularly oxygen management, during general anesthesia in Japan. All adult patients (16 yr old or older) who received general anesthesia over 5 consecutive days in 2015 at 43 participating hospitals were identified. Ventilator settings and vital signs were collected 1 h after the induction of general anesthesia. We determined the prevalence of potentially preventable hyperoxemia (oxygen saturation measured by pulse oximetry of more than 98%, despite fractional inspired oxygen tension of more than 0.21) and the risk factors for potentially substantial oxygen exposure (fractional inspired oxygen tension of more than 0.5, despite oxygen saturation measured by pulse oximetry of more than 92%). Results: A total of 1, 786 patients were found eligible, and 1, 498 completed the study. Fractional inspired oxygen tension was between 0.31 and 0.6 in 1, 385 patients (92%), whereas it was less than or equal to 0.3 in very few patients (1%). Most patients (83%) were exposed to potentially preventable hyperoxemia, and 32% had potentially substantial oxygen exposure. In multivariable analysis, old age, emergency surgery, and one-lung ventilation were independently associated with increased potentially substantial oxygen exposure, whereas use of volume control ventilation and high positive end-expiratory pressure levels were associated with decreased potentially substantial oxygen exposure. One-lung ventilation was particularly a strong risk factor for potentially substantial oxygen exposure (adjusted odds ratio, 13.35; 95% CI, 7.24 to 24.60). Conclusions: Potentially preventable hyperoxemia and substantial oxygen exposure are common during general anesthesia, especially during one-lung ventilation. Future research should explore the safety and feasibility of a more conservative approach for intraoperative oxygen therapy. Abstract : In this multicenter, cross-sectional study of 1, 498 patients at 43 hospitals, potentially preventable hyperoxemia and substantial oxygen exposure were common during general anesthesia, especially in patients receiving one-lung ventilation.Supplemental Digital Content is available in the text.